2014
DOI: 10.1073/pnas.1322200111
|View full text |Cite
|
Sign up to set email alerts
|

Dimer recognition and secretion by the ESX secretion system inBacillus subtilis

Abstract: Protein secretion typically involves translocation of unfolded polypeptides or transport of monomeric folded proteins. Here we provide, to our knowledge, the first experimental evidence for secretion of an intact multimeric complex requiring a signal formed by both members of the complex. Using systematic mutagenesis of a substrate involved in early secretory antigen 6 kDa (ESX) secretion in Bacillus subtilis, we demonstrate that export of the substrate requires two independent motifs. Using mixed dimers, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 35 publications
6
81
0
Order By: Relevance
“…Homologs of the mycobacterial T7SS that transport WXG100 proteins have also been described in firmicutes, including Bacillus anthracis (32), Bacillus subtilis (33), and Staphylococcus aureus (14). Firmicutes carry some (EsxA, EsxB, and EccC), but not all, of the mycobacterial ESX-1 components required for secretion of ESAT-6 and CFP-10 (34), and their pathways are designated type VIIb (29).…”
Section: Discussionmentioning
confidence: 99%
“…Homologs of the mycobacterial T7SS that transport WXG100 proteins have also been described in firmicutes, including Bacillus anthracis (32), Bacillus subtilis (33), and Staphylococcus aureus (14). Firmicutes carry some (EsxA, EsxB, and EccC), but not all, of the mycobacterial ESX-1 components required for secretion of ESAT-6 and CFP-10 (34), and their pathways are designated type VIIb (29).…”
Section: Discussionmentioning
confidence: 99%
“…Although a second potential 5 WXG100 substrate YfjA was identified in B. subtilis genome [10], there is no 6 evidence that the associated protein is exported in a YukBA-dependent 7 fashion [57,58]. Utilizing this simple Bacillus system Sysoeva et al [35] 8 demonstrated that YukE was secreted as a homodimer, and that the WXG100 9 motif and a C-terminal sequence are required for its secretion. Intriguingly, 10…”
Section: Type VII Secretion In Bacillus 12mentioning
confidence: 99%
“…secretion signal formed by both the WXG100 and C-terminal motifs, each 1 contributed by individual subunits of the substrate dimer [35]. Given the 2 conservation of these motifs across type VII substrates, they likely play a 3 crucial role in controlling type VIIb secretion [6].…”
mentioning
confidence: 99%
“…"Type VII" secretion systems distantly related to mycobacterial ESX systems have been identified in numerous other Gram-positive bacteria (13)(14)(15)(16)(17). The protein components of type VII secretion systems differ considerably between bacterial species but generally include the following: (i) one or more small helical proteins of the WXG100 protein family (e.g., ESAT-6, YukE), (ii) an FtsK/SpoIII-type ATPase that is thought to drive protein secretion (e.g., EccC, YukB), and (iii) a multipass transmembrane protein that may form the pore of the translocon (e.g., EccD, YueB).…”
mentioning
confidence: 99%